Human resource quality, work professionalism, and commitment as a supporting factor improving employee performance kultura digital media publishing in Surakarta - Dasmadi Dasmadi; Asih Handayani (Enrichment : Journal of Management, 2023)
This research aims to determine the quality of human resources, work professionalism, commitment and their influence on employee performance. on the performance of Kultura Digital Media (KDM) publishing employees in Surakarta city both partially and simultaneously. The research approach used in this study is a quantitative approach. The population in the company amounted to 100 permanent employees and 50 people were taken as respondents. 50 people were taken as respondents with the sampling method used was simple random sampling or simple random sampling by means of a lottery / simple random sample. Simple random sampling by means of a lottery / draw from the names of KDM Surakarta employees who were then taken as many as the sample used, namely 50 people. draw as much as the sample used, namely 50 names of employees selected in the draw. Data analysis method using multiple linear regression analysis. The results of testing and analysis conducted state that the quality of human resources has a positive and significant effect on performance. quality of human resources has a positive and significant effect on the performance of KDM employees, work professionalism has a positive and significant effect on the performance of KDM employees. professionalism has a positive and significant effect on the performance of KDM employees and commitment has a positive and significant effect on the performance of KDM employees.and significant to the performance of KDM employees. Simultaneously the quality of human resources,professionalism, and commitment support the performance of KDM employees.